2017
DOI: 10.1021/acs.analchem.7b02969
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Surface Area of Nanosheet Graphene Oxide Colloid Using a Gas-Phase Electrostatic Approach

Abstract: We demonstrate a new, facile gas-phase electrostatic approach to successfully quantify equivalent surface area of graphene oxide (GO) colloid on a number basis. Mobility diameter (d)-based distribution and the corresponding equivalent surface area (SA) of GO colloids (i.e., with different lateral aspect ratios) were able to be identified by electrospray-differential mobility analysis (ES-DMA) coupled to a condensation particle counter (CPC) and an aerosol surface area analyzer (ASAA). A correlation of SA ∝ d w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Because of the presence of oxygen, GO is more hydrophilic than pure G, and can more easily disperse in organic solvents, water, and different matrices [23], [24]. Recently, basic studies on the physicochemical properties GO, have shown that the hydrophilicity [25], mechanical strength [26], high surface area [27] and adhesive forces [28] are related to how the G sheets interact with each other. This interaction can occur by π-π stacking of [29], electrostatic or ionic interactions, and van der Waals forces depending on the exact structure of the functionalized sheets.…”
Section: Graphene Oxide In Bone Tissue Engineeringmentioning
confidence: 99%
“…Because of the presence of oxygen, GO is more hydrophilic than pure G, and can more easily disperse in organic solvents, water, and different matrices [23], [24]. Recently, basic studies on the physicochemical properties GO, have shown that the hydrophilicity [25], mechanical strength [26], high surface area [27] and adhesive forces [28] are related to how the G sheets interact with each other. This interaction can occur by π-π stacking of [29], electrostatic or ionic interactions, and van der Waals forces depending on the exact structure of the functionalized sheets.…”
Section: Graphene Oxide In Bone Tissue Engineeringmentioning
confidence: 99%
“…After exiting the electrospray aerosol generator, the MOF aerosols with a neutralized charge distribution were delivered to an electrostatic classifier (model 3081, TSI Inc.) for size classification. An entire mobility size distribution can be obtained by varying the electric field applied to the electrostatic classifier (i.e., determined on the basis of the force balance between the electrostatic and the drag forces exerting on an aerosol particle). The number concentration of aerosol particles with a specific mobility diameter ( d p,m ) was counted by using a n-butanol-based condensation particle counter (CPC, model 3775, TSI Inc.). A sheath air flow rate ( Q sheath ) of 10.0 L/min was used for delivering aerosol particle downstream in the electrostatic classifier, and the step size and the step time used in the mobility size measurements were 2.0 nm and 5.0 s, respectively. Additional descriptions of the system design are shown in Section S1 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Q aerosol and Q L are the filtered air flow (1.5 L/min) and the liquid flow through 40-μm fused silica capillary (i.e., estimated to be 4.3 × 10 −7 L/min). 23,24 Here, d p,m,max and d p,m,min are the maximum and the minimum values of the d p,m bounding to the peak of the analyzed population, respectively. dd p is the size increment in correspondence to the selected d p,m .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface was determined by the DFT method and corresponds to (26.6 ± 2.6) m 2 ·g –1 . Usually, the GO surface area according to the literature data is estimated to be 200–600 m 2 ·g –1 , , and the low surface area is due to the association of the layers via hydrogen bonds. Similar results were previously obtained by Ding et al for GO obtained from the waste graphite from diamond synthesis industry.…”
mentioning
confidence: 99%